Public health-relevant consequences of the COVID-19 pandemic on malaria in sub-Saharan Africa: a scoping review - Heuschen, Anna-Katharina; Lu, Guangyu; Razum, Oliver; Abdul-Mumin, Alhassan; Sankoh, Osman A.; von Seidlein, Lorenz; D’Alessandro, Umberto; Müller, Olaf (Malaria journal, 2021)
The COVID-19 pandemic has resulted in unprecedented challenges to health systems worldwide, including the control of non-COVID-19 diseases. Malaria cases and deaths may increase due to the direct and indirect effects of the pandemic in malaria-endemic countries, particularly in sub-Saharan Africa (SSA). This scoping review aims to summarize information on public health-relevant effects of the COVID-19 pandemic on the malaria situation in SSA.
Gesehen am 12.05.2022